Application of Fuzzy Mathematics in Predicting Rainfall - Shahi, Nirak Kumar; Rana, Keshar Singh; Paudel, Gyan Prasad; Bhatt, Mohan Raj; Baral, Aasis; Devkota, Hemanta (Journal of Physical and Life Sciences, 2024)
Fuzzy Logic is a multiple valued logic, from which the truth values of variables might be any real numbers between 0 and 1. It has wide application in different fields of real life. We might face different challenges in our daily life to deal with vagueness and uncertainty. There are various criteria in the literature for decision-making under uncertainty in a crisp environment. In this paper, we address the relation between temperature, humidity and rainfall with the help of Mamdani fuzzy inference system.